Migración temporal vs. permanente: análisis de la migración de colombianos a Brasil, 2007-2015 (2018)
The main objective of this paper consists in analyzing the actual situation of Colombian migrations in Brazil, exposing the two main phenomena as it is the temporary and the permanent migration. This document aims to study the main main reasons why temporary migration of Colombians to Brazil tends to prevail over permanent migration. For this, the migratory fluxes in education and work will be taken as the main sources, focusing on the period between 2007 and 2015. This work expects to be as a useful tool for understanding the main trends of migrations to Brazil and the role of Colombian inmigrants in this phenomenon; purpose considered an important effort to complement the studies on the third Colombian wave of migration.